PENGARUH SKIN HEALTH LITERACY DAN COSMETIC SAFETY AWARENESS TERHADAP PERILAKU PEMILIHAN KOSMETIKA DALAM PENCEGAHAN MASALAH KULIT WAJAH - Nofilia Sacharum; Junaidi Malik (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Facial skin problems remain a common public health concern, often influenced by consumers' behavior in selecting cosmetic products. Limited skin health literacy and low awareness of cosmetic safety may increase the risk of using inappropriate or unsafe cosmetics. This study aimed to examine the influence of Skin Health Literacy and Cosmetic Safety Awareness on cosmetic selection behavior for the prevention of facial skin problems among residents of Blokagung, Banyuwangi. A quantitative study with a cross-sectional design was conducted involving 120 cosmetic users as the study population. A total of 92 respondents were selected using simple random sampling. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression in IBM SPSS Statistics 26. The results revealed that Skin Health Literacy had a positive and significant effect on cosmetic selection behavior (β = 0.462; t = 4.876; p < 0.001). Cosmetic Safety Awareness also showed a positive and significant effect (β = 0.381; t = 3.945; p < 0.001). Simultaneously, both variables significantly influenced cosmetic selection behavior (F = 41.562; p < 0.001), with an Adjusted R² of 0.472. The findings indicate that improving skin health literacy and cosmetic safety awareness can encourage safer cosmetic selection behavior and contribute to the prevention of facial skin problems.